Solusi Numerik Model Dinamik Perlakuan Immunotherapy pada Infeksi HIV-1 - Kartono, Agus; Rosidah, Rosidah; Arif, Ardian (BERKALA FISIKA, 2010)
There are several types of treatment options that can slow the progression of HIV that can be offered if the number of CD4 + cells has been known for certain, one treatment is by immunotherapy with interleukin-2 (IL-2). This type of treatment is to increase the immune system that can help the body fight against the infection itself. Efforts to raise an immune response would be appropriate to reduce the amount of virus. This brings new hope for treatment of HIV infection and the type of treatment is being researched. Interleukin-2 (IL-2) is most of the cytokines which are proteins made by the body. T-helper cells, a type of white blood cells, produce IL-2 when they were stimulated by infection. In this study, a model of HIV disease progression than individuals not treated can be expressed in a mathematical model, and also expressed immunotherapy model to see the dynamics of viral populations and the population of CD4 + T cells from HIV disease based on ordinary differential equation (ODE). This study aims to calculate the numerical solution immunotherapy mathematical model in HIV infection and a mathematical model to predict the outcome of immunotherapy treatment strategies in HIV infection. Keywords: HIV, CD4 + T cells, immunotherapy, mathematical modeling